Post-Translational Modifications of BRD4: Therapeutic Targets for Tumor - Liu, Na; Ling, Rui; Tang, Xiang; Yu, Yunpeng; Zhou, Yuepeng; Chen, Deyu (Frontiers in Oncology, 2022)
Bromodomain-containing protein 4 (BRD4), a member of the bromodomain and extraterminal (BET) family, is considered to be a major driver of cancer cell growth and a new target for cancer therapy. Over 30 targeted inhibitors currently in preclinical and clinical trials have significant inhibitory effects on various tumors, including acute myelogenous leukemia (AML), diffuse large B cell lymphoma, prostate cancer, breast cancer and so on. However, resistance frequently occurs, revealing the limitations of BET inhibitor (BETi) therapy and the complexity of the BRD4 expression mechanism and action pathway. Current studies believe that when the internal and external environmental conditions of cells change, tumor cells can directly modify proteins by posttranslational modifications (PTMs) without changing the original DNA sequence to change their functions, and epigenetic modifications can also be activated to form new heritable phenotypes in response to various environmental stresses. In fact, research is constantly being supplemented with regards to that the regulatory role of BRD4 in tumors is closely related to PTMs. At present, the PTMs of BRD4 mainly include ubiquitination and phosphorylation; the former mainly regulates the stability of the BRD4 protein and mediates BETi resistance, while the latter is related to the biological functions of BRD4, such as transcriptional regulation, cofactor recruitment, chromatin binding and so on. At the same time, other PTMs, such as hydroxylation, acetylation and methylation, also play various roles in BRD4 regulation. The diversity, complexity and reversibility of posttranslational modifications affect the structure, stability and biological function of the BRD4 protein and participate in the occurrence and development of tumors by regulating the expression of tumor-related genes and even become the core and undeniable mechanism. Therefore, targeting BRD4-related modification sites or enzymes may be an effective strategy for cancer prevention and treatment. This review summarizes the role of different BRD4 modification types, elucidates the pathogenesis in the corresponding cancers, provides a theoretical reference for identifying new targets and effective combination therapy strategies, and discusses the opportunities, barriers, and limitations of PTM-based therapies for future cancer treatment.